Production and marketing of chili in the Brong-Ahafo area of Ghana - Vigneri, Marcella; Kolavalli, Shashidhara; Agandin, John; Moyo, Qondi (International Food Policy Research Institute, 2021)
This paper provides an in-depth account of the chili value chain in the Brong Ahafo area of Ghana, looking at the agronomic practices of producers, marketing choices by chili type, and practices of traders along different commercial corridors. Using original survey data of producers and traders, the paper addresses two questions: Are there opportunities to increase the productivity of chilies? Does the marketing system deliver a significant share of the consumer prices to producers? Chili yields are less than 1.0 mt/ha against a yield potential in Ghana of nearly 8 mt/ha. Long chili growers in the top 10 percentile by yields harvested nearly 18 bags compared to the average of 11 bags per acre obtained by all producers. These higher chili yields resulted primarily by applying higher levels of inorganic fertilizers. Many producers have adopted improved chili varieties – nearly 70 percent of long chili producers reported having planted Legon 18, the variety which is generally used for making chili powder. Producers also reported maintaining their crop in the field for unusually long periods to extend their production into leaner production periods. Prices vary geographically by day and by marketing channel. The margins earned by traders on the sale price of their chilis range from 20 to 100 percent under different conditions. The chili value chain is short. The bulk of chilis produced reaches consumers with only one intermediary between producer and consumer. Fresh and dry chilies are marketed differently. Nearly 80 percent of dry chili producers sell at their farm gate, where they tend to obtain prices that are higher than those received by producers who take their dry chilies to markets. The reverse is true for fresh chili producers, however. It is plausible that producers choose between producing dry long or fresh round chilies depending on their marketing ability. Social networks influence the choice by producers of what traders to engage with, suggesting that producers with stronger ties to traders obtain higher prices.